Attitude toward Christianity, sexual orientation, and parental religiosity in a sample of Italian adolescents - Baiocco, Roberto (Journal of beliefs and values, 2018)
Literature suggests that several demographic variables are linked with religiosity in adolescence, such as gender, age and parental religiosity. The sample consisted of 910 young people (53% female) between 14 and 19 years of age, attending secular secondary schools in Rome, Italy. They self-identified as heterosexual adolescents (91.6%), and lesbian/gay (LG) adolescents (8.4%). High scores of positive attitudes toward God, Jesus, the Bible, prayer and church were associated with female gender, higher father's religiosity, and higher mother's religiosity, but not with age of the participants. As expected, heterosexual orientation was associated with a more positive attitude toward Christianity, controlling for sex, age, and parental religiosity.